Are the Markets Vertically Integrated? : Evidence on Shallot marketing channels in Gorontalo Province, Indonesia. - Bakari, Yuliana; Moonti, Agustinus; Olabu, Riskawati (AIBPM Publisher, 2024)
The vertical market integration of the shallot market system in Gorontalo Province is a method that can be used to estimate the price movements at each level of marketing (farmers, marketing agents, and consumers), thereby facilitating long-run and short-run equilibrium. Therefore, this study aims to analyze the vertical market integration formed between marketing channels for the shallot market in Gorontalo Province. The Engel-Granger cointegration method was used to analyze long-run equilibrium, while ECM (Error Correction Models) was utilized for short-run equilibrium estimation. The cointegration test results showed that markets at farmer and marketing agent levels, marketing agent and consumer levels, as well as farmer and consumer levels, were cointegrated. This indicated the presence of long-run equilibrium and vertical market integration. The ECM test results revealed that in the short-run equilibrium, markets at farmer and marketing agent levels, marketing agent and consumers levels, as well as farmer and consumer levels were integrated within an estimated adjustment time of one month. Based on these findings, the shallot marketing system in Gorontalo Province was vertically integrated between the marketing agents involved